Skip to main content

Advertisement

Degenerate binomial coefficients and degenerate hypergeometric functions

Abstract

In this paper, we investigate degenerate versions of the generalized pth order Franel numbers which are certain finite sums involving powers of binomial coefficients. In more detail, we introduce degenerate generalized hypergeometric functions and study degenerate hypergeometric numbers of order p. These numbers involve powers of λ-binomial coefficients and λ-falling sequence, and can be represented by means of the degenerate generalized hypergeometric functions. We derive some explicit expressions and combinatorial identities for those numbers. We also consider several related special numbers like λ-hypergeometric numbers of order p and Apostol type λ-hypergeometric numbers of order p, of which the latter reduce in a limiting case to the generalized pth order Franel numbers.

Introduction

First, we study certain finite sums involving powers of binomial coefficients which are called generalized pth order Franel numbers and can be represented in terms of hypergeometric functions. Then, among other things, we find that particular cases of these numbers are connected with many known special numbers and polynomials which include Bernoulli numbers, Euler numbers, Changhee numbers, Daehee numbers, Stirling numbers of the first kind, Catalan numbers, and Legendre polynomials.

In recent years, many mathematicians have devoted their attention to studying various degenerate versions of some special numbers and polynomials [4, 7, 8, 10, 15, 16]. The idea of investigating degenerate versions of some special numbers and polynomials originated from Carlitz’s papers [2, 3]. Indeed, he introduced the degenerate Bernoulli and Euler polynomials and numbers, and investigated some arithmetic and combinatorial aspects of them. Here we mention in passing that the degenerate Bernoulli polynomials were later rediscovered by Ustinov under the name of Korobov polynomials of the second kind. Two of the present authors, their colleagues, and some other people have studied quite a few degenerate versions of special numbers and polynomials with their interest not only in combinatorial and arithmetic properties but also in differential equations and certain symmetric identities (see [9, 16] and the references therein). It is worth noting that this idea of considering degenerate versions of some special polynomials and numbers is not only limited to polynomials but can also be extended to transcendental functions like gamma functions [11, 12]. We believe that studying some degenerate versions of special polynomials and numbers is a very fruitful and promising area of research in which many things remain yet to be uncovered.

Recently, Dolgy and Kim gave some explicit formulas of degenerate Stirling numbers associated with the degenerate special numbers and polynomials. Motivated by Dolgy and Kim’s paper [4], we would like to investigate degenerate versions of the generalized pth order Franel numbers. In more detail, we introduce degenerate generalized hypergeometric functions and study degenerate hypergeometric numbers of order p. These numbers involve powers of λ-binomial coefficients and λ-falling sequence, and can be represented by means of the degenerate generalized hypergeometric functions. We also consider several related special numbers like λ-hypergeometric numbers of order p and Apostol type λ-hypergeometric numbers of order p, of which the latter reduce in a limiting case to the generalized pth order Franel numbers.

For the rest of this section, we will fix some notations and recall some known results that are needed throughout this paper.

For \(\lambda\in\mathbb{R}\), the degenerate exponential function is defined as

$$ e_{\lambda}^{x}(t)=(1+\lambda t)^{\frac{x}{\lambda }},\quad \quad e_{\lambda}(t)=(1+\lambda t)^{\frac{1}{\lambda}}=e_{\lambda }^{1}(t)\quad \bigl(\text{see [2, 3, 11, 12, 14]}\bigr). $$
(1)

From (1), we note that

$$ e_{\lambda}^{x}(t)=\sum _{n=0}^{\infty}(x)_{n,\lambda }\frac{t^{n}}{n!}\quad\bigl( \text{see [4, 9--12]}\bigr), $$
(2)

where \((x)_{n,\lambda}\) is the λ-falling sequence given by

$$ (x)_{0,\lambda}=1,\qquad(x)_{n,\lambda}=x(x-\lambda )\cdots \bigl(x-(n-1)\lambda\bigr)\quad(n\ge1). $$
(3)

In [10], the degenerate Stirling numbers of the second kind are defined by

$$ \frac{1}{k!}\bigl(e_{\lambda}(t)-1\bigr)^{k}= \sum_{n=k}^{\infty }S_{2,\lambda}(n,k) \frac{t^{n}}{n!}\quad(k\ge0). $$
(4)

Let

$$ (x)_{0}=1,\qquad(x)_{n}=x(x-1) (x-2)\cdots \bigl(x-(n-1)\bigr)\quad (n\ge1). $$
(5)

Then \(\lim_{\lambda\rightarrow0}S_{2,\lambda}(n,k)=S_{2}(n,k) \), where \(S_{2}(n,k)\) are the ordinary Stirling numbers of the second kind given by

$$ x^{n}=\sum_{l=0}^{n}S_{2}(n,l) (x)_{l}\quad(n\ge0)\quad \bigl(\text{see [1--13, 15--22]}\bigr). $$
(6)

The Stirling numbers of the first kind are defined as

$$ \frac{1}{k!} \bigl(\log(1+t) \bigr)^{k}=\sum _{n=k}^{\infty }S_{1}(n,k) \frac{t^{n}}{n!}\quad(k\ge0)\text{ }\bigl(\text{see [13, 15]}\bigr). $$
(7)

Thus, by (7), we get

$$ (x)_{n}=\sum_{l=0}^{n}S_{1}(n,l)x^{l} \quad(n\ge0). $$
(8)

In view of (4), the degenerate Stirling numbers of the first kind are defined by

$$ \frac{1}{k!} \biggl(\frac{(1+t)^{\lambda}-1}{\lambda } \biggr)^{k}= \sum_{n=k}^{\infty}S_{1,\lambda}(n,k) \frac {t^{n}}{n!}\quad\bigl(\text{see [4, 10]}\bigr). $$
(9)

Note that \(\lim_{\lambda\rightarrow0}S_{1,\lambda }(n,k)=S_{1}(n,k)\) (\(n,k\ge0\)).

As is well known, the generalized hypergeometric function \(F^{(p,q)}\) is defined by

F(p,q)(a1,a2,,apb1,b2,,bq|x)=k=0a1kapkb1kb2kbqkxkk!,
(10)

where \(\langle a\rangle_{k}=a(a+1)\cdots(a+(k-1))\) (\(k\ge1\)), \(\langle a\rangle_{0}=1\) (see [17, 21]).

For example,

F(2,1)(1,bb|1)=12,F(2,1)(2,bb|1)=14,F(2,1)(3,bb|1)=18,.

The Gauss summation theorem is given by

F(2,1)(a,bc|1)=Γ(c)Γ(cab)Γ(ca)Γ(cb),
(11)

where \(R(c)>R(b)>0\), \(R(c-a-b)>0\), \(R(c)>R(a)>0\).

From (11), we note that

F(2,1)(a,bc|z)=Γ(c)Γ(b)Γ(cb)01tb1(1t)cb1(1tz)adt,
(12)

where \(R(c)>R(b)>0\).

The following are well-known identities related to the binomial coefficients:

$$\begin{aligned}& \sum_{k=0}^{n} \binom{n}{k}=2^{n}\quad(n\ge0), \end{aligned}$$
(13)
$$\begin{aligned}& \sum_{k=0}^{n}(-1)^{k} \binom{n}{k}=0\quad(n\ne0, n\in \mathbb{N}), \end{aligned}$$
(14)
$$\begin{aligned}& \sum_{k=0}^{n} \binom{n}{k}^{2}=\frac {(2n)!}{(n!)^{2}}=\binom{2n}{n}, \end{aligned}$$
(15)
$$\begin{aligned}& \sum_{k=0}^{n}(-1)^{k} \binom{n}{k}^{3}=\left \{ \textstyle\begin{array}{l@{\quad}l} 0,& \textrm{if }n\textrm{ is odd,}\\ \frac {(-1)^{n/2}n!}{ ((\frac{n}{2})! )^{2}}, &\textrm{otherwise}, \end{array}\displaystyle \right . \end{aligned}$$
(16)
$$\begin{aligned}& \sum_{k=-n}^{n}(-1)^{k} \binom{n+b}{n+k}\binom {n+c}{c+k}\binom{b+c}{b+k}=\frac{\varGamma(b+c+n+1)}{n!\varGamma (b+1)\varGamma(c+1)}. \end{aligned}$$
(17)

Sums of powers of λ-binomial coefficients

The λ-binomial coefficients are defined as

$$ \binom{x}{n}_{\lambda}=\frac{(x)_{n,\lambda}}{n!}= \frac {x(x-\lambda)\cdots(x-(n-1)\lambda)}{n!}\quad(n\ge1),\qquad\binom {x}{0}_{\lambda}=1\quad( \lambda\in\mathbb{R}). $$
(18)

From (18), we easily get

$$ \binom{x+y}{n}_{\lambda}=\sum _{l=0}^{n}\binom {x}{l}_{\lambda} \binom{y}{n-l}_{\lambda}\quad(n\ge0). $$
(19)

By (1), we easily get

$$ B_{\lambda}^{*}(n,k)=\frac{d^{n}}{dt^{n}} \bigl(e_{\lambda }(t)+1 \bigr)^{k}\bigg|_{t=0}=\sum _{j=1}^{k}\binom {k}{j}(j)_{n,\lambda}, $$
(20)

where n and k are positive integers.

Note that \(\lim_{\lambda\rightarrow0}B_{\lambda}^{*}(n,k)=B(n,k)\), where \(B(n,k)\) are defined by Golombek and given by

$$ B(n,k)=\sum_{j=1}^{k}\binom{k}{j}j^{n} \quad\bigl(\text{see [5, 6]}\bigr). $$

Now, we define the degenerate hypergeometric function as

Fλ(a,bc|z)=n=0an,λbn,λcn,λznn!,
(21)

where \(\langle a\rangle_{n,\lambda}=a(a+\lambda)\cdots (a+(n-1)\lambda)\) (\(n\ge1\)), \(\langle a\rangle_{0,\lambda}=1\).

From (21), we note that

Fλ(n,nλ|λeλ(t))=k=0nk,λnk,λλkλk,λeλk(t)k!=k=0(n)k,λ(n)k,λk!eλk(t)k!=k=0(nk)λ2eλk(t)=m=0k=0(nk)λ2(k)m,λtmm!,
(22)

where n is a nonnegative integer.

Let us define

Fλ(n,nλ|λeλ(t))=m=0Qλ(m,2)tmm!.
(23)

Therefore, by (22) and (23), we obtain the following theorem.

Theorem 2.1

For\(m\ge0\), we have

$$ Q_{\lambda}(m,2)=\sum_{k=0}^{\infty} \binom{n}{k}_{\lambda }^{2}(k)_{m,\lambda}. $$

We note that \(\lim_{\lambda\rightarrow0}Q_{\lambda}(m,2)=\sum_{k=0}^{n}\binom{n}{k}^{2}k^{m}=Q(m,2) \), which was introduced by Golombek and Marburg (see [5, 6]).

We observe that

Fλ(a×|z)=k=0ak,λ(z)kk!=k=0(a)k,λk!zk=k=0(ak)λzk=eλa(z).

For \(n\in\mathbb{N}\), let

Fλ(n×|eλ(t))=(1+λeλ(t))nλ=m=0Hλ(n,m)tmm!.
(24)

On the one hand, we have

$$\begin{aligned} \bigl(1+\lambda e_{\lambda}(t)\bigr)^{\frac{n}{\lambda}}=\sum _{k=0}^{\infty}\binom{n}{k}_{\lambda}e^{k}_{\lambda}(t)= \sum_{m=0}^{\infty} \Biggl(\sum _{k=0}^{\infty}\binom{n}{k}_{\lambda }(k)_{m,\lambda} \Biggr)\frac{t^{m}}{m!}. \end{aligned}$$
(25)

On the other hand, we get

$$\begin{aligned} \bigl(1+\lambda e_{\lambda}(t)\bigr)^{\frac{n}{\lambda}}& = \bigl(1+\lambda+\lambda\bigl(e_{\lambda}(t)-1\bigr) \bigr)^{\frac{n}{\lambda}} \\ &=(1+\lambda)^{\frac{n}{\lambda}} \biggl(1+\frac{\lambda }{1+\lambda} \bigl(e_{\lambda}(t)-1\bigr) \biggr)^{\frac{n}{\lambda}} \\ &= (1+\lambda)^{\frac{n}{\lambda}}\sum_{k=0}^{\infty } \binom{n}{k}_{\lambda} \biggl(\frac{1}{1+k} \biggr)^{k} \bigl(e_{\lambda }(t)-1\bigr)^{k} \\ &=(1+\lambda)^{\frac{n}{\lambda}}\sum_{k=0}^{\infty }(n)_{k,\lambda} \biggl(\frac{1}{1+\lambda} \biggr)^{k}\frac {1}{k!} \bigl(e_{\lambda}(t)-1\bigr)^{k} \\ &=\sum_{m=0}^{\infty} \Biggl((1+ \lambda)^{\frac{n}{\lambda }}\sum_{k=0}^{m}(n)_{k,\lambda} \biggl(\frac{1}{1+\lambda} \biggr)^{k}S_{2,\lambda}(m,k) \Biggr) \frac{t^{m}}{m!}. \end{aligned}$$
(26)

From (24), (25), and (26), we obtain the following theorem.

Theorem 2.2

For\(n\in\mathbb{N}\)and\(m\in\mathbb{N}\cup\{0\}\), we have

$$ H_{\lambda}(n,m)=(1+\lambda)^{\frac{n}{\lambda}}\sum _{k=0}^{m}(n)_{k,\lambda} \biggl( \frac{1}{1+\lambda} \biggr)^{k}S_{2,\lambda}(m,k)=\sum _{k=0}^{\infty}\binom{n}{k}_{\lambda }(k)_{m,\lambda}. $$

As is well known, the degenerate Bell polynomials are defined by

$$ e_{\lambda}^{x}\bigl(e_{\lambda}(t)-1\bigr)= \sum_{n=0}^{\infty }\operatorname{Bel}_{n,\lambda}(x) \frac{t^{n}}{n!}\quad\bigl(\text{see [16]}\bigr). $$
(27)

By (27), we easily get

$$ \operatorname{Bel}_{n,\lambda}(x)=\sum _{k=0}^{n}(x)_{k,\lambda}S_{2,\lambda}(n,k) \quad(n\ge0). $$
(28)

Now, we define the degenerate bivariate Bell polynomials by

$$ e_{\lambda}^{x} \bigl(y\bigl(e_{\lambda}(t)-1 \bigr) \bigr)=\sum_{n=0}^{\infty} \operatorname{Bel}_{n,\lambda}(x,y)\frac{t^{n}}{n!}. $$
(29)

Thus, by (29), we get

$$ \operatorname{Bel}_{n,\lambda}(x,y)=\sum _{k=0}^{n}(x)_{k,\lambda}y^{k}S_{2,\lambda}(n,k) \quad(n\ge0). $$
(30)

From Theorem 2.2 and (30), we obtain the following corollary.

Corollary 2.3

For\(n\in\mathbb{N}\)and\(m\in\mathbb{N}\cup\{0\}\), we have

$$ H_{\lambda}(n,m)=(1+\lambda)^{\frac{n}{\lambda}}\operatorname {Bel}_{m,\lambda} \biggl(n,\frac{1}{1+\lambda} \biggr). $$

Note that

$$ \lim_{\lambda\rightarrow0}H_{\lambda}(n,m)=\sum _{k=0}^{\infty }\frac{n^{k}}{k!}k^{m}=e^{n} \sum_{k=0}^{m}n^{k}S_{2}(m,k). $$

We observe that

$$\begin{aligned} H_{\lambda}(n,1)&=\sum_{k=0}^{\infty} \binom {n}{k}_{\lambda}(k)_{1,\lambda}=\sum _{k=1}^{\infty}\frac {(n)_{k,\lambda}}{(k-1)!} \\ &=\sum_{k=0}^{\infty} \binom {n}{k}_{\lambda}(n-k\lambda)=n\sum_{k=0}^{\infty} \binom {n}{k}_{\lambda}-\lambda\sum_{k=0}^{\infty} \binom{n}{k}_{\lambda }k \\ &=n\sum_{k=0}^{\infty} \binom{n}{k}_{\lambda}-\lambda H_{\lambda}(n,1). \end{aligned}$$
(31)

Thus, by (31), we get

$$ (1+\lambda)H_{\lambda}(n,1)=n\sum _{k=0}^{\infty}\binom {n}{k}_{\lambda}=n(1+ \lambda)^{\frac{n}{\lambda}}. $$
(32)

From (32), we have

$$ H_{\lambda}(n,1)=n(1+\lambda)^{\frac{n}{\lambda}-1} \quad(\lambda \neq-1 ). $$

For \(m=2\), we have

$$ \begin{aligned}[b]\sum_{k=0}^{\infty} \binom{n}{k}_{\lambda}(k)_{2,\lambda }&=\sum _{k=0}^{\infty}\frac{(n)_{k,\lambda}}{k!}k(k-\lambda)=\sum _{k=1}^{\infty}\frac{(n)_{k,\lambda}}{(k-1)!}(k-\lambda) \\ &=\sum_{k=1}^{\infty} \frac{(n)_{k,\lambda}}{(k-1)!}(k-1+1-\lambda) =\sum_{k=2}^{\infty} \frac{(n)_{k,\lambda}}{(k-2)!}+(1-\lambda)\sum_{k=1}^{\infty} \frac{(n)_{k,\lambda}}{(k-1)!} \\ &=\sum_{k=2}^{\infty} \frac{(n-2\lambda)_{k-2,\lambda }}{(k-2)!}n(n-\lambda)+(1-\lambda)n\sum_{k=1}^{\infty} \frac {(n-\lambda)_{k-1,\lambda}}{(k-1)!} \\ &=n(n-\lambda)\sum_{k=2}^{\infty} \binom{n-2\lambda }{k-2}_{\lambda}+n(1-\lambda)\sum_{k=1}^{\infty} \binom{n-\lambda }{k-1}_{\lambda} \\ &=n(n-\lambda)\sum_{k=0}^{\infty} \binom{n-2\lambda }{k}_{\lambda}+n(1-\lambda)\sum_{k=0}^{\infty} \binom{n-\lambda }{k}_{\lambda} \\ &=n(n-\lambda) (1+\lambda)^{\frac{n}{\lambda }-2}+n(1-\lambda) (1+ \lambda)^{\frac{n}{\lambda}-1} \\ &=n\bigl(n+1-\lambda-\lambda^{2}\bigr) (1+ \lambda)^{\frac{n}{\lambda}-2}.\end{aligned} $$
(33)

By (33), we get

$$ H_{\lambda}(n,2)=n(n+1-2\lambda) (1+\lambda)^{\frac {n}{\lambda}-2}. $$
(34)

Let us take \(m=3\). Then we have

$$\begin{aligned} H_{\lambda}(n,3)&=\sum_{k=0}^{\infty} \binom{n}{k}_{\lambda }(k)_{3,\lambda}=\sum _{k=0}^{\infty}\binom{n}{k}_{\lambda }k(k- \lambda) (k-2\lambda) \\ &=\sum_{k=1}^{\infty}\frac{(n)_{k,\lambda}}{(k-1)!}(k- \lambda ) (k-2\lambda)=\sum_{k=1}^{\infty} \frac{(n)_{k,\lambda }}{(k-1)!}(k-1+1-\lambda) (k-2\lambda) \\ &=\sum_{k=2}^{\infty} \frac{(n)_{k,\lambda}}{(k-2)!}(k-2 \lambda )+(1-\lambda)\sum_{k=1}^{\infty} \frac{(n)_{k,\lambda }}{(k-1)!}(k-2\lambda) \\ & =\sum_{k=3}^{\infty} \frac{(n)_{k,\lambda}}{(k-3)!}+3(1- \lambda )\sum_{k=2}^{\infty}\frac{(n)_{k,\lambda}}{(k-2)!}+(1- \lambda ) (1-2\lambda)\sum_{k=1}^{\infty} \frac{(n)_{k,\lambda}}{(k-1)!} \\ &=(n)_{3,\lambda}\sum_{k=0}^{\infty} \binom{n-3\lambda}{k}_{\lambda }+3(1-\lambda) (n)_{2,\lambda}\sum _{k=0}^{\infty}\binom{n-2\lambda }{k}_{\lambda} \\ &\quad+(1-\lambda) (1-2\lambda) (n)_{1,\lambda}\sum _{k=0}^{\infty }\binom{n-\lambda}{k}_{\lambda} \\ &=(n)_{3,\lambda}(1+\lambda)^{\frac{n}{\lambda}-3}+3(1-\lambda ) (n)_{2,\lambda}(1+\lambda)^{\frac{n}{\lambda}-2}+(1-\lambda ) (1-2\lambda)n(1+ \lambda)^{\frac{n}{\lambda}-1}. \end{aligned}$$

Note that

$$ \lim_{\lambda\rightarrow1}H_{\lambda}(n,3)=\sum _{k=0}^{n}\binom {n}{k}(k)_{3}=(n)_{3}2^{n-3} $$

and

$$ \lim_{\lambda\rightarrow0}H _{\lambda}(n,3)=\sum _{k=0}^{\infty }\frac{n^{k}}{k!}k^{3}=n \bigl(n^{2}+3n+1\bigr)e^{n}. $$

For \(s\in\mathbb{C}\) with \(R(s)>0\), the gamma function is defined by

$$ \varGamma(s)= \int_{0}^{\infty}e^{-t}t^{s-1}\,dt. $$

Let n be a nonnegative integer. Then

$$ \frac{\langle b\rangle_{n,\lambda}}{\langle c\rangle_{n,\lambda }}=\frac{\varGamma (\frac{b}{\lambda}+n )\varGamma (\frac {c}{\lambda} )}{\varGamma (\frac{c}{\lambda}+n )\varGamma (\frac{b}{\lambda} )}, $$

where \(R (\frac{c}{\lambda} )>0\) and \(R (\frac {b}{\lambda} )>0\).

For \(R (\frac{c}{\lambda} )>R (\frac{b}{\lambda} )>0\), we have

$$ \frac{\varGamma (\frac{b}{\lambda}+n )\varGamma (\frac{c}{\lambda}-\frac{b}{\lambda} )}{\varGamma (\frac {c}{\lambda}+n )}= \int_{0}^{1}t^{\frac{b}{\lambda }+n-1}(1-t)^{\frac{c}{\lambda}-\frac{b}{\lambda}-1}\,dt. $$
(35)

From (35), we note that

Fλ(a,bc|z)=n=0an,λbn,λcn,λznn!=Γ(cλ)Γ(bλ)Γ(cλbλ)01tbλ1(1t)cλbλ1(1λtz)aλdt.
(36)

In particular, for \(z=\frac{1}{\lambda}\) (\(\lambda\ne0\)), from (11) we get

Fλ(a,bc|1λ)=Γ(cλ)Γ(cλbλaλ)Γ(cλbλ)Γ(cλaλ),where R(cλbλaλ)>0.
(37)

For \(n\in\mathbb{N}\), by (37), we get

Fλ(n,nλ|1λ)=Γ(1)Γ(1+2nλ)Γ(1+nλ)Γ(1+nλ)=2λnΓ(2nλ)(Γ(nλ))2,
(38)

where λ is a positive real number.

On the other hand,

Fλ(n,nλ|1λ)=k=0nk,λnk,λλk,λ(1λ)kk!=k=0λ2k(nk)λ2.
(39)

Therefore, by (38) and (39), we obtain the following theorem.

Theorem 2.4

Letλbe a positive real number. For\(n\in\mathbb{N}\), we have

$$ \sum_{k=0}^{\infty}\lambda^{-2k} \binom{n}{k}_{\lambda}^{2}=\frac {2\lambda}{n} \frac{\varGamma (\frac{2n}{\lambda} )}{ (\varGamma (\frac{n}{\lambda} ) )^{2}}. $$

Note that

$$ \lim_{\lambda\rightarrow1}\sum_{k=0}^{\infty} \lambda^{-2k}\binom {n}{k}^{2}_{\lambda}=\sum _{k=0}^{n}\binom{n}{k}^{2}= \frac {(2n)!}{(n!)^{2}}=\binom{2n}{n}. $$

Now, we define the degenerate generalized hypergeometric function as

Fλ(p,q)(a1,a2,,apb1,,bq|z)=k=0a1k,λapk,λb1k,λbqk,λzkk!,where |z|<1.
(40)

Let n be a positive integer. Then we define the degenerate hypergeometric numbers of orderp by

Fλ(p,p1)(nn,,nλ,,λ|(1)pλp1eλ(t))=m=0Hλ(p)(n,m)tmm!.
(41)

From (23) and (24), we note that \(H_{\lambda }(n,m)=H_{\lambda}^{(1)}(n,m)\), and \(Q_{\lambda}(m,2)=H_{\lambda }^{(2)}(n,m)\).

In (40), we note that

Fλ(p,p1)(n,n,,nλ,,λ|(1)pλp1eλ(t))=k=0nk,λnk,λnk,λλk,λλk,λλk,λ(1)pkλ(p1)kk!eλk(t)=k=0((n)k,λ)p(k!)p1eλk(t)k!=k=0(nk)λpeλk(t)=m=0(k=0(nk)λp(k)m,λ)tmm!.
(42)

Therefore, by (41) and (42), we obtain the following theorem.

Theorem 2.5

For\(n,p\in\mathbb{N}\)and\(m\in\mathbb{N}\cup\{0\}\), we have

$$ H_{\lambda}^{(p)}(n,m)=\sum_{k=0}^{\infty} \binom{n}{k}_{\lambda }^{p}(k)_{m,\lambda}. $$

Note that

$$ \lim_{\lambda\rightarrow1}H_{\lambda}^{(p)}(n,m)=\sum _{k=0}^{n}\binom{n}{k}^{p}(k)_{m} \quad\text{and}\quad\lim_{\lambda\rightarrow0}H_{\lambda}^{(p)}(n,m)= \sum_{k=0}^{\infty }\frac{n^{kp}}{(k!)^{p}}k^{m}. $$

From (42), we note that

Fλ(p,p1)(n,n,,nλ,,λ|(1)pλp1eλ(t))=k=0(nk)λpeλk(t)=k=0(nk)λpl=0k(kl)(eλ(t)1)l=k=0(nk)λpl=0k(k)lm=lS2,λ(m,l)tmm!=m=0(k=0l=0k(nk)λp(k)lS2,λ(m,l))tmm!.
(43)

Therefore, by (41) and (43), we obtain the following theorem.

Theorem 2.6

For\(n,p\in\mathbb{N}\)and\(m\in\mathbb{N}\cup\{0\}\), we have

$$ H_{\lambda}^{(p)}(n,m)=\sum_{k=0}^{\infty} \sum_{l=0}^{k}\binom {n}{k}_{\lambda}^{p}(k)_{l}S_{2,\lambda}(m,l). $$

By (41) and (42), we get

Hλ(p)(n,0)=k=0(nk)λp=Fλ(p,p1)(n,n,,nλ,,λ|(1)pλp1).

Note that

k=0n(nk)p=limλ1Hλ(p)(n,0)=F(p,p1)(n,n,,n1,,1|(1)p).

From (40), we have

Fλ(p,p1)(n,n,,nλ,,λ|(λ)p1eλ(t))=k=0(nk)λp(1)keλk(t)=m=0(k=0(nk)λp(1)k(k)m,λ)tmm!.
(44)

Thus, by (44), we get

Fλ(p,p1)(n,n,,nλ,,λ|(λ)p1)=k=0(nk)λp(1)k.
(45)

Note that

limλ1Fλ(p,p1)(n,n,,nλ,,λ|(λ)p1)=k=0n(nk)p(1)k=F(p,p1)(n,n,,n1,,1|(1)p1).

Further remarks

Let n be a positive integer. From (10), we have

F(2,1)(n,n1|eλ(t))=k=0nknk1keλk(t)k!=k=0n(nk)2eλk(t)=m=0(k=0n(nk)2(k)m,λ)tmm!.
(46)

Now, we define the λ-hypergeometric numbers of orderp by

F(p,p1)(n,n,,n1,,1|(1)peλ(t))=m=0Hm,λ(p)(n)tmm!.
(47)

By (46) and (47), we get

$$ H_{m,\lambda}^{(2)}(n)=\sum _{k=0}^{n}\binom {n}{k}^{2}(k)_{m,\lambda}, $$
(48)

where \(n\in\mathbb{N}\) and \(m\in\mathbb{N}\cup\{0\}\).

The alternatingλ-hypergeometric numbers of orderp are defined by

F(p,p1)(n,n,,n1,,1|(1)p1eλ(t))=m=0Tm,λ(p)(n)tmm!.
(49)

By (10), we get

F(2,1)(n,n1|eλ(t))=m=0(k=0(nk)2(1)k(k)m,λ)tmm!.
(50)

From (49) and (50), we have

$$ T_{m,\lambda}^{(2)}(n)=\sum _{k=0}^{n}\binom {n}{k}^{2}(-1)^{k}(k)_{m,\lambda}, $$
(51)

where \(m\in\mathbb{N}\cup\{0\}\) and \(n\in\mathbb{N}\).

In general, we have

$$ T_{m,\lambda}^{(p)}(n)=\sum_{k=0}^{n} \binom {n}{k}^{p}(-1)^{k}(k)_{m,\lambda}\quad \text{and}\quad H_{m,\lambda }^{(p)}(n)=\sum _{k=0}^{n}\binom{n}{k}^{p}(k)_{m,\lambda}, $$

where \(n,p\in\mathbb{N}\) and \(m\in\mathbb{N}\cup\{0\}\).

We observe that

F(1,0)(n×|eλ(t))=k=0n(nk)eλk(t)
(52)

and

F(1,0)(n×|eλ(t))=k=0n(nk)(1)keλk(t).
(53)

Thus, we note that

$$ H_{m,\lambda}^{(1)}(n)=\sum_{k=0}^{n} \binom{n}{k}(k)_{m,\lambda },\qquad T_{m,\lambda}^{(1)}=\sum _{k=0}^{n}\binom {n}{k}(-1)^{k}(k)_{m,\lambda}, $$

where \(m\in\mathbb{N}\cup\{0\}\) and \(n\in\mathbb{N}\).

For example,

$$\begin{aligned}& H_{0,\lambda}^{(1)}(n)=2^{n},\qquad H_{1,\lambda}^{(1)}(n)=n2^{n-1}, \qquad H_{2,\lambda}^{(1)}(n)=n(n+1-2\lambda)2^{n-2}, \\& H_{3,\lambda}^{(1)}(n)=(n)_{3}2^{n-3}+3(n)_{2}(1- \lambda )2^{n-2}+n(1-\lambda)_{2,\lambda}2^{n-1},\dots, \\& T_{0,\lambda}^{(1)}(n)=0,\qquad T_{1,\lambda}^{(1)}(n)=- \delta _{1,n}, \\& T_{2,\lambda}^{(1)}(n)=n(n-1)\delta_{2,n}+(\lambda-1) \delta_{n,1}, \ldots, \end{aligned}$$

where \(\delta_{n,k}\) is Kronecker’s symbol.

From (49), we note that

m=0Tm,λ(1)(n)tmm!=F(1,0)(n×|eλ(t))=(1eλ(t))n=(1)nn!n!(eλ(t)1)n=(1)nn!m=nS2,λ(m,n)tmm!.
(54)

On the other hand,

$$ \bigl(1-e_{\lambda}(t)\bigr)^{n}=\sum _{j=0}^{n}\binom {n}{j}(-1)^{n-j}e_{\lambda}^{j}(t)= \sum_{m=0}^{\infty} \Biggl(\sum _{j=0}^{n}\binom{n}{j}(-1)^{n-j}(j)_{m,\lambda} \Biggr)\frac{t^{m}}{m!}. $$
(55)

Thus, by (54) and (55), we get

$$ T_{m,\lambda}^{(1)}(n)=\sum _{j=0}^{n}\binom {n}{j}(-1)^{n-j}(j)_{m,\lambda}=(-1)^{n}n!S_{2,\lambda}(m,n) \quad (m\ge n). $$
(56)

If \(m< n\), then \(T_{m,\lambda}^{(1)}(n)=0\).

Theorem 3.1

For\(n\in\mathbb{N}\)and\(m\in\mathbb{N}\cup\{0\}\), we have

$$ T_{m,\lambda}^{(1)}(n)=\sum_{j=0}^{n} \binom {n}{j}(-1)^{n-j}(j)_{m,\lambda}=(-1)^{n}n!S_{2,\lambda}(m,n) \quad (m\ge n). $$

In particular, if\(m< n\), then

$$ T_{m,\lambda}^{(1)}=0. $$

For \(k\ge0\), we have

$$ \lim_{\lambda\rightarrow0}(-1)^{n}T_{n+k,\lambda}^{(1)}(n)= \sum_{j=0}^{n}\binom{n}{j}(-1)^{j}j^{n+k}=n!S_{2}(n+k,n). $$

Corollary 3.2

For\(k\ge0\)and\(n\in\mathbb{N}\), we have

$$ \frac{1}{n!}\sum_{j=0}^{n} \binom{n}{j}(-1)^{j}j^{n+k}=S_{2}(n+k,n). $$

It is easy to show that

$$\begin{aligned} \bigl(e^{t}-1\bigr)^{n} &=\sum _{j=0}^{n}\binom{n}{j}(-1)^{n-j}e^{jt} \\ &=\sum_{j=0}^{n}\sum _{l=0}^{j}\binom{n}{j}(-1)^{n-j}(j)_{l} \frac {1}{l!}\bigl(e^{t}-1\bigr)^{l} \\ &=\sum_{j=0}^{n}\sum _{l=0}^{j}\binom{n}{j}(j)_{l}(-1)^{n-j} \sum_{m=l}^{\infty}S_{2}(m,l) \frac{t^{m}}{m!}. \end{aligned}$$

Thus, we have

$$ \sum_{m=n}^{\infty}S_{2}(m,n) \frac{t^{m}}{m!}=\frac {1}{n!}\bigl(e^{t}-1\bigr)^{n} =\frac{1}{n!}\sum_{j=0}^{n}\sum _{l=0}^{j}\binom {n}{j}(j)_{l}(-1)^{n-j} \sum_{m=l}^{\infty}S_{2}(m,l) \frac{t^{m}}{m!}. $$
(57)

For \(k\ge0\), \(n\in\mathbb{N}\), by (57), we get

$$ S_{2}(n+k,n)=\frac{1}{n!}\sum _{j=0}^{n}\sum_{l=0}^{n+k} \binom{n}{j}(j)_{l}(-1)^{n-j}S_{2}(n+k,l). $$
(58)

From Corollary 3.2 and (58), we have

$$ \sum_{j=0}^{n}\binom{n}{j}(-1)^{j}j^{n+k}= \sum_{j=0}^{n}\sum _{l=0}^{n+k}\binom{n}{j}(j)_{l}(-1)^{n-j}S_{2}(n+k,l). $$

For \(\lambda,\lambda_{1}\in\mathbb{R}\), let us define Apostol type alternatingλ-hypergeometric numbers of orderp by

F(p,p1)(n,n,,n1,,1|(1)p1λ1eλ(t))=m=0Tm,λ(p)(n|λ1)tmm!.
(59)

By (10), we get

F(1,0)(n×|λ1eλ(t))=k=0n(nk)(λ1eλ(t))k=j=0n(nj)(1)jλ1jeλj(t)=m=0(j=0n(nj)(1)jλ1j(j)m,λ)tmm!.
(60)

On the other hand,

F(1,0)(n×|λ1eλ(t))=(1λ1eλ(t))n=j=0n(nj)(1)jλ1jeλj(t)=j=0n(nj)(1)jλ1jl=0j(jl)(eλ(t)1)l=j=0nl=0j(nj)(1)jλ1j(j)l(eλ(t)1)ll!=j=0nl=0j(nj)(1)jλ1j(j)lm=lS2,λ(m,l)tmm!.
(61)

For \(k\ge0\) and \(n\in\mathbb{N}\), by (59), (60), and (61), we obtain the following theorem.

Theorem 3.3

For\(\lambda,\lambda_{1}\in\mathbb{R}\), \(n\in\mathbb{N}\), and\(k\in \mathbb{N}\cup\{0\}\), we have

$$ T_{n+k,\lambda}^{(1)}(n \mid\lambda_{1})=\sum _{j=0}^{n}\binom {n}{j}(-1)^{j} \lambda_{1}^{j}(j)_{n+k,\lambda}=\sum _{j=0}^{n}\sum_{l=0}^{j} \binom{n}{j}(-1)^{j}\lambda_{1}^{j}(j)_{l}S_{2,\lambda}(n+k,l). $$

Note that

$$ \lim_{\lambda\rightarrow0}T_{n+k,\lambda}^{(1)}(n \mid\lambda _{1})=\sum_{j=0}^{n} \binom{n}{j}(-1)^{j}\lambda_{1}^{j}j^{n+k}= \sum_{j=0}^{n}\sum _{l=0}^{j}\binom{n}{j}(-1)^{j} \lambda _{1}^{j}(j)_{l}S_{2}(n+k,l). $$

For \(\lambda_{1}\in\mathbb{R}\), let us define Apstol–Stirling numbers of the second kind as

$$ \frac{1}{n!} \bigl(\lambda_{1}e^{t}-1 \bigr)^{n}=\sum_{m=0}^{\infty}S(m,n\mid \lambda_{1})\frac{t^{m}}{m!}\quad(n\ge0). $$
(62)

Now, we observe that

$$ \frac{1}{n!}\bigl(\lambda_{1}e^{t}-1 \bigr)^{n}=\frac{1}{n!}\sum_{j=0}^{n} \binom{n}{j}\lambda_{1}^{j}(-1)^{n-j}e^{jt}= \frac {1}{n!}\sum_{j=0}^{n} \binom{n}{j}\lambda_{1}^{j}(-1)^{n-j}\sum _{m=0}^{\infty}j^{m}\frac{t^{m}}{m!}. $$
(63)

For \(k\in\mathbb{N}\cup\{0\}\) and \(n\in\mathbb{N}\), by (62) and (63), we get

$$ S(n+k, n \mid\lambda_{1})=\frac{(-1)^{n}}{n!}\sum _{j=0}^{n}\binom{n}{j} \lambda_{1}^{j}(-1)^{j}j^{n+k}. $$
(64)

From Theorem 3.3 and (64), we have

$$ \lim_{\lambda\rightarrow0}T_{n+k,\lambda}^{(1)}(n \mid \lambda_{1})=(-1)^{n}n!S(n+k,n \mid\lambda_{1})= \sum_{j=0}^{n}\binom{n}{j} \lambda_{1}^{j}(-1)^{j}j^{n+k}. $$
(65)

Therefore, by (65), we obtain the following corollary.

Corollary 3.4

For\(k\in\mathbb{N}\cup\{0\}\)and\(n\in\mathbb{N}\), we have

$$ \sum_{j=0}^{n}\binom{n}{j}\lambda _{1}^{j}(-1)^{j}j^{n+k}=(-1)^{n}n!S(n+k,n \mid\lambda)=\lim_{\lambda \rightarrow0}T_{n+k,\lambda}^{(1)}(n \mid \lambda_{1}). $$

Remarks

  1. (a)

    Corollary 3.4 naturally interprets the sum in Corollary 3.4 in terms of Apostol–Stirling numbers of the second kind defined by (62).

  2. (b)

    For \(\lambda,\lambda_{1}\in\mathbb{R}\), let us define Apostol typeλ-hypergeometric numbers of orderp by

    F(p,p1)(n,n,,n1,,1|(1)pλ1eλ(t))=m=0Hm,λ(p)(nλ1)tmm!.
    (66)

    By (10), we get

    F(p,p1)(n,n,,n1,,1|(1)pλ1eλ(t))=k=0(nk)pλ1keλk(t)=m=0(k=0n(nk)pλ1k(k)m,λ)tmm!.
    (67)

    From (66) and (67), we have

    $$ H_{m,\lambda}^{(p)}(n \mid\lambda_{1})=\sum _{k=0}^{n}\binom {n}{k}^{p} \lambda_{1}^{p}(k)_{m,\lambda},\quad\text{where } n,p\in \mathbb{N} \text{ and } m\in\mathbb{N}\cup\{0\}. $$

    Note that

    $$ \lim_{\lambda\rightarrow0}H_{m,\lambda}^{(p)}(n\mid\lambda _{1})=\sum_{k=0}^{n} \binom{n}{k}^{p}\lambda_{1}^{p}k^{m}. $$

Conclusion

In this paper, we studied certain finite sums involving powers of binomial coefficients which are called generalized pth order Franel numbers and can be represented in terms of hypergeometric functions. Then, among other things, we found that particular cases of these numbers are connected with many known special numbers and polynomials which include Bernoulli numbers, Euler numbers, Changhee numbers, Daehee numbers, Stirling numbers of the first kind, Catalan numbers, and Legendre polynomials. Recently, Dolgy and Kim gave some explicit formulas of degenerate Stirling numbers associated with the degenerate special numbers and polynomials. Motivated by Dolgy and Kim’s paper [4], we investigated degenerate versions of the generalized pth order Franel numbers. In more detail, we introduced degenerate generalized hypergeometric functions and studied degenerate hypergeometric numbers of order p. We showed that the degenerate hypergeometric numbers of order p involve powers of λ-binomial coefficients and λ-falling sequence, and can be represented by means of the degenerate generalized hypergeometric functions. We also considered several related special numbers like λ-hypergeometric numbers of order p and Apostol type λ-hypergeometric numbers of order p, of which the latter reduce in a limiting case to the generalized pth order Franel numbers.

References

  1. 1.

    Agarwal, P., Younis, J.A., Kim, T.: Certain generating functions for the quadruple hypergeometric series \(K_{10}\). Notes Number Theory Discrete Math. 25(4), 16–23 (2019)

  2. 2.

    Carlitz, L.: A degenerate Staudt–Clausen theorem. Arch. Math. (Basel) 7, 28–33 (1956)

  3. 3.

    Carlitz, L.: Degenerate Stirling, Bernoulli and Eulerian numbers. Util. Math. 15, 51–88 (1979)

  4. 4.

    Dolgy, D.V., Kim, T.: Some explicit formulas of degenerate Stirling numbers associated with the degenerate special numbers and polynomials. Proc. Jangjeon Math. Soc. 21(2), 309–317 (2018)

  5. 5.

    Golombek, R.: Aufgabe 1088. Elem. Math. 49, 126–127 (1994)

  6. 6.

    Golombek, R., Marburg, D.: Aufgabe 1088, Summen mit Quadraten von Binomialkoeffizienten. Elem. Math. 50, 125–131 (1995)

  7. 7.

    Haroon, H., Khan, W.A.: Degenerate Bernoulli numbers and polynomials associated with degenerate Hermite polynomials. Commun. Korean Math. Soc. 33(2), 651–669 (2018)

  8. 8.

    He, Y., Araci, S.: Sums of products of Apostol–Bernoulli and Apostol–Euler polynomials. Adv. Differ. Equ. 2014, Article ID 155 (2014)

  9. 9.

    Kim, D.S., Kim, H.Y., Kim, D., Kim, T.: Identities of symmetry for type 2 Bernoulli and Euler polynomials. Symmetry 11, Article ID 613 (2019)

  10. 10.

    Kim, T.: A note on degenerate Stirling polynomials of the second kind. Proc. Jangjeon Math. Soc. 20(3), 319–331 (2017)

  11. 11.

    Kim, T., Jang, G.-W.: A note on degenerate gamma function and degenerate Stirling number of the second kind. Adv. Stud. Contemp. Math. (Kyungshang) 28(2), 207–214 (2018)

  12. 12.

    Kim, T., Kim, D.S.: Degenerate Laplace transform and degenerate gamma function. Russ. J. Math. Phys. 24(2), 241–248 (2017)

  13. 13.

    Kim, T., Kim, D.S.: A note on type 2 Changhee and Daehee polynomials. Rev. R. Acad. Cienc. Exactas Fís. Nat., Ser. A Mat. 113(3), 2783–2791 (2019)

  14. 14.

    Kim, T., Kim, D.S., Kwon, J.: A note on λ-hypergeometric random variables. Rev. Educ. 387(2), 49–52 (2020)

  15. 15.

    Kim, T., Yao, Y., Kim, D.S., Jang, G.W.: Degenerate-Stirling numbers and r-Bell polynomials. Russ. J. Math. Phys. 25(1), 44–58 (2018)

  16. 16.

    Pyo, S.-S., Kim, T.: Some identities of fully degenerate Bell polynomials arising from differential equations. Proc. Jangjeon Math. Soc. 22(2), 357–363 (2019)

  17. 17.

    Rainville, E.D.: Special Functions. Chelsea, New York (1971)

  18. 18.

    Rim, S.-H., Kim, T., Lee, S.H.: Some symmetry identities for \((h,q)\)-Bernoulli polynomials under the third dihedral group \(D_{3}\) arising from q-Volkenborn integral on \(\mathbb{Z}_{p}\). J. Comput. Anal. Appl. 20(3), 432–436 (2016)

  19. 19.

    Rim, S.-H., Kim, T., Pyo, S.-S.: Identities between harmonic, hyperharmonic and Daehee numbers. J. Inequal. Appl. 2018, Article ID 168 (2018)

  20. 20.

    Roman, S.: The Umbral Calculus. Pure and Applied Mathematics, vol. 111. Academic Press, New York (1984)

  21. 21.

    Whittaker, E.T., Watson, G.N.: Modern Analysis, 4th edn. Cambridge University Press, Cambridge (1927)

  22. 22.

    Zhang, W., Lin, X.: Identities involving trigonometric functions and Bernoulli numbers. Appl. Math. Comput. 334, 288–294 (2018)

Download references

Acknowledgements

The authors would like to thank the anonymous reviewers for their valuable comments and suggestions which helped us improve the quality of our work.

Availability of data and materials

Not applicable.

Funding

This work was supported by the National Research Foundation of Korea (NRF) grant funded by the Korea government (MEST) (No. 2017R1E1A1A03070882).

Author information

TK and DSK conceived of the framework and structured the whole paper; DSK and TK wrote the paper; JK paid the article processing charge for the paper; HL typed the paper; DSK and TK completed the revision of the article. All authors have read and agreed to the published version of the manuscript.

Correspondence to Jongkyum Kwon.

Ethics declarations

Competing interests

The authors declare no conflict of interest.

Additional information

Publisher’s Note

Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.

Rights and permissions

Open Access This article is licensed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article’s Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article’s Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence, visit http://creativecommons.org/licenses/by/4.0/.

Reprints and Permissions

About this article

Verify currency and authenticity via CrossMark

Cite this article

Kim, T., Kim, D.S., Lee, H. et al. Degenerate binomial coefficients and degenerate hypergeometric functions. Adv Differ Equ 2020, 115 (2020). https://doi.org/10.1186/s13662-020-02575-3

Download citation

MSC

  • 11B73
  • 11B83
  • 33C70

Keywords

  • Degenerate hypergeometric function
  • Degenerate bivariate Bell polynomials
  • Degenerate hypergeometric numbers of order p
  • λ-Hypergeometric numbers of order p